Cultural influences on group learning in an ESL classroom - Arumugam, Nalini; Rafik-Galea, Shameem; De Mello, Geraldine; Dass, Laura Christ (Canadian Center of Science and Education, 2013)
This study investigated the role of learners’ culture in their choice of learning preference. It took a closer look at how students cultural norms influenced collaborative writing performance. A survey approach was employed via a questionnaire and semi-structured interviews to tringulate the findings. Two Institutions were involved in this study, Institutin A comprised of Malay learners while Chinese learners represented Instituion B. The findings suggest that students’ learning is embedded in rich culture and attributes and as they interacted in their groups, they demonstrated positive values such as unity, tolerance, obedience and respectfulness. These values were more obvious among learners in Institution A. These leaners revealed that since young they have been instilled to practice and appreciate their culture and customs and this was seen in the way they interacted in the classroom. The students were sharing ideas politely and practising their cultural values even in the academic context. A few self-centred learners also changed their social behaviour from a selfish attitude to a more sharing and accommodating behaviour by the end of the study. At Institution B, some learners demonstrated positive values like unity and sharing attitude but they did not practice them throughout their group work. They were more individualistic and preferred individual work. It was apparent that the students’ cultural virtues transcended from the social to the academic setting and have become a part of their life. This paper concludes that cooperative group work is effective because of the students’ embedded values and culture, and that culture is a dominant controlling factor that impacts one’s way of learning and communicating in a formal ESL academic setting.